Військово-політичні аспекти розвитку Першої Болгарської держави в ІХ – першій чверті Х ст. - Калініченко, Віталій (Чернівці, Чернівецький національний університет імені Юрія Федьковича, 2017)
The study of military-political history of the population of Central-Eastern and Southeastern Europe in the early Middle Ages is one of the important tasks of historical science. The key to contemporary historiography remains the study of problems associated with the political history of states, which in the Middle Ages had a developed military organization and significantly influenced the militant culture of neighboring nations. In IX-th – the first third of the X-th century one of the most powerful countries in the military plan was the First Bulgarian Empire, its organization of troops which had a significant influence on the development of political and social processes both within the country itself and the formation of military culture of various state formations during the IX-th-X-th centuries. The investigation of issues of Bulgarian studies as a branch of Slavic studies from the very beginning of its formation in the late XVIII-th – the middle of the XIX-th century contained a number of aspects of a controversial nature, which at the beginning of the XXI-th century require further research attention of scientists. First of all, it concerns the definition of the borders of the Bulgarian Empire, the range of its military culture, as well as the mutual influence of the Bulgarians in the military aspect with other peoples. In the above-mentioned discourse, issues related to the military-administrative policy of the First Bulgarian Empire in the region under study are objectively updated. The large-scale expansion of the Danube Bulgarians led to the massive militarization of local Slavs, as a result of which they were drawn into various military-political conflicts of that time. The study of the military history of the Danube Bulgaria in 800-927 years makes it possible to investigate the evolution of its military affairs, which contributes to a deep understanding of the geopolitical strategy of the state of the Bulgarians, the understanding of sociopolitical processes in the neighboring territories, as well as the definition of the nature of relations between border state entities on the basis of comparison of that time military culture. In chapter 1 «Historiography, source base and theoretical and methodological principles of the study» the degree of scientific development of the problem in the works of domestic and foreign researchers has been clarified, the theoretical and methodological principles of work have been outlined. In accordance with the problem-chronological principle, the analysis of foreign and domestic historical works related to the problems of the military-political history of the First Bulgarian Empire in IX-th – the first third of the Х-th century has been proposed. The historiography of the problem is divided into 3 groups: generalizing works on the military-political history of the Bulgarian state; works related to the principles of internal organization of the Bulgarian army and labor related to the armament of the Danube Bulgarian troops, their tactics and strategies. Chapter 2 «The role of a political factor in the formation of the armed forces of the Danube Bulgaria», contains a presentation of events relating to military-political history and the formation of the military organization of the First Bulgarian Empire in the under study period. The geopolitical changes in the Carpatho-Balkan region which were related to the military expansion of the Danube Bulgarians to the northern, western and southern territories north of the Danube River, to the Middle Danube, the Black Sea and the Dnipro in the first half of the IX-th century, as well as with the war policy of the Frankish Empire against the Avar Kaganate, which conquer the latter and promote the Franks in Tysa. In addition, the author considers the religious factor, which since the 50’s and 60’s of the IXth century made a significant impact on the geopolitical situation in the Carpatho-Balkan region as a whole. Also, attention was paid to the relationship with Great Moravia and the East-Frankish kingdom in the 60-s and 70-s of the IX-th century, as well as the campaign in 883 Bulgarian troops to Tysa. The dyssertant also analyzed the military-political activities of King Simeon I, whose rule was that Danube Bulgaria significantly expanded its borders to the south, south-west and west of the Balkan Peninsula. In chapter 3 «Structural-organizational principles of the Bulgarian army and principles of its functioning», the formation of the military-administrative system of the Bulgarian state, the principles of manning, the number and ethnic composition of the Bulgarian army and the structures of the leadership of the armed forces have been analyzed. It was established that the military discipline in the army's configuration was the result of the creation of a multi-ethnic, numerous, well-armed, equipped and motivated army. During IX-th – the first third of the X-th century by the conquest of various states and peoples, the bulgarians attracted them to their troops and spread their own military culture on the conquered lands. It is proved that in the IX-th century Bulgaria was a monarchy with a structured, centralized management apparatus headed by a khan, who had unlimited power and served administrative and military functions. Chapter 4 «Arms and military art of the First Bulgarian Empire» analyzed the formation of a complex of weapons in the Danube Bulgarian army, their tactics and strategy. The dyssertant proved, that the formation of the complex of armaments of the Danube Bulgarians took place by the conquest of various states, by the borrowing of various types of weapons and the militarization of the population. Also attention is paid to the characteristics of fire-metal weapons and machines for the siege of fortifications. Concepts of the military strategy of the troops of the Bulgarian rulers are clearly traceable in hostilities with the Byzantine Empire. The economic resources, political and territorial actions of Byzantium were the main strategic priorities of the Bulgarian rulers. It was established that the tactics of the troops of the Danube Bulgarians was similar to tactical receptions of other nomads: Avars, Khozars, Ugrics and Pechenigs. The main tactical techniques of the Bulgarians in the course of military confrontation was the enemy’s environment, the organization of ambushes and maneuvering, since the main impetus of the Danube Bulgarians was a cavalry. The conclusions of the of the dissertation summarize the main provisions and results of the research. It was established that the period of 800-927 years in the military-political history of the First Bulgarian Empire was marked by important evolutionary changes. During this time the Bulgarian rulers substantially expanded the borders of their state. In the first half of the nineteenth century there have been significant changes in the military culture of the local population of the Carpathian region, which were associated with the large-scale military expansion of the Bulgarian state to the northern, western and southern lands along the Danube River to the upper reaches of the Dnister, Prut and Tysa rivers. The consequence of these campaigns was the conquest of large areas of the territory in which the Slavic population lived. These hikes played a key role and became a catalyst for the formation of a military organization of the Bulgarian army, which was based on the proto-Bulgarian and Slavic components. It has been substantiated that a clear administrative system of the Bulgarian state, created in the era of Khan Krum, has defined the basic principles of the military organization of the Bulgarians. At the beginning of the nineteenth century the acquisition of military formations was carried out only for a specific purpose. The core of the Bulgarian army consisted of proto-Bulgarians, who, if necessary, were provided with assistance by Slavic military contingents, who had their own tribal organization. The inclusion in the military system of the Slavic population, which lived in the Tysa and Dnister interfluves, significantly influenced the militarization of the population throughout the Carpatho-Balkan region. Military discipline in the process of completing the troops of the Bulgarian state was the result of the creation of a large, heterogeneous and well-armed army, which was constantly in different parts of the country and showed readiness to go on a trip, to fight for war or to protect state borders in a short time. The dyssertant found that the increase of the holdings of the Bulgarian state at the expense of the conquered lands in the Carpatho-Balkan region led to the creation of a clear, regulated management system in different parts of the country. Most of the posts in the hierarchical structure of the Danube Bulgaria provided the combination and execution of two functions: administrative and military. Their organic combination allowed the Bulgarian rulers to create a branched, disciplined hierarchical structure for the management of armed units and separate territories of the Bulgarian Empire. It was found that the placement and establishment of Bulgarian military contingents on conquered lands led to the creation of a centralized supply and supply system for weapons in certain regions. Available archaeological materials suggest that since the beginning of the nineteenth century the Slavic population, the Tysa-Dnister interfluves massively militarized as a result of the spread of Bulgarian military culture among the Slavs. These interactions were traced back to the 20’s of the IX-th century and by the end of the 30’s of the X-th century – when in the Carpatho-Balkan region continued constant military operations, which involved local people. The author proved that the large-scale expansion of the Bulgarian rulers in the first half of the IX-th century on different territories of the Danube-Dnister interfluves marked changes in the distribution of various types of weapons among local Slavs. Formation of the armed forces of the Danube Bulgarians took place by the conquest of neighboring states, by the borrowing of arms and militarization of local population, in particular the Slavs, which actively participated in the Bulgarian state’s wars and gradually became acquainted with new types of arms. It was established that the Bulgarian militarist strategy depended on the military experience that the army gained in wars with neighboring states and peoples. Characteristic features of the military strategy of the rulers of the Danube Bulgarians are traced in military operations with the Byzantine Empire during the IX-th-X-th centuries. The economic resources, political and territorial actions of Byzantium were the main strategic goal of the Bulgarian rulers. They also tried to conquer large territories in the Carpatho-Balkan region and to militarize the local population, primarily Slavic. This gave the Bulgarians the opportunity to fight with other state formations and tribal associations in the Tysa-Dnister interfluves. Strategically important was the issue of political consolidation of the Bulgarians with other Slavic unions, which was solved through the implementation of administrative-territorial reforms by the Bulgarian khans Krum and Omurtag and due to the massive involvement of the Slavs in the Bulgarian military-administrative system. In addition, it was arguably proved that the military policy implemented by the rulers of the Danube Bulgaria, as well as the military experience acquired by the Bulgarians in the wars of the VII-th-VIII-th centuries near the Dnipro, the Black Sea and the Azov Sea, the involvement of the numerous Slavic ethnic component in its own foreign policy, contacts with the military culture of the people who lived in the Tysa-Dnipro interfluves, and familiarization with new types of weapons identified further tactical methods of combat the actions of the Bulgarian troops. Constant wars by the Bulgarian state with Avars, Khazars, Byzantium, Serbia, Croatia, Great Moravia, Frankish Empire, Ugrics and Pechenigs, taking into account regional geopolitical specifics, undeniably influenced on the acquisition of military experience and the improvement of tactics in the conduct of wars and the conquest of European territories. The basic tactical techniques of the troops of the Danube Bulgarians in the course of the military confrontation were the enemy’s environment, the organization of ambushes and maneuvering, since their main shock was the cavalry. As a result of the consideration of the issues, related to the military-political history of the First Bulgarian State in the years 800-927, it was found that this research was carried out for the first time. The practical value of the work lies in the fact that the collected and systematized factual material can be involved in the writing of scientific papers on world history, in the compilation of thematic training and teaching aids, the preparation of special courses on military history and the historical past of the Slavic peoples of the Middle Ages. The results of the study can be used for lectures and practical classes in higher education institutions of the III-d-IV-th levels of accreditation, in school courses of history, ethnographic work.
Military-political aspects of the development of the First Bulgarian Empire in IX – the first quarter of the X-th century
Keywords: Перша Болгарська держава; Карпато-Балканський регіон; Аварський каганат; слов'яни; протоболгари; військова справа; озброєння; тактика; стратегія